Table 2_Patient-needs-enhanced emergency nursing assessment framework accelerates time-critical care for non-traumatic chest pain.docx - Yan Sun (22436) (2025)
Background Non-traumatic chest pain requires rapid Emergency Department (ED) triage, yet adherence to ECG ≤10 min and early troponin targets is inconsistent, standard nursing frameworks seldom prompt patient-needs that affect timeliness and documentation. The aim of this study is to determine whether implementing a patient-needs-enhanced Emergency Nursing Assessment Framework (ENAF), compared with usual care, increases the proportion of ED patients with non-traumatic chest pain receiving a 12-lead ECG within 10 min. Methods This prospective single-center quasi-experimental before-after study was conducted in the T Third Affiliated Hospital of Naval Medical University from January 2023 to January 2025 and assigned to a control group and ENAF group. The ENAF group comprised (1) eight hours of nurse training, (2) an ENAF electronic template incorporating mandatory pain, anxiety, information-need and social-support items, and (3) a triage “rapid chest-pain kit”. The primary endpoint was completion of a 12-lead ECG within 10 min of triage; secondary endpoints were door-to-troponin time, ≥2-point pain reduction at 30 min, documentation completeness, ED length of stay (LOS) and 30-day major adverse cardiac events (MACE). Multivariable logistic regression adjusted for age, sex, HEART score, arrival mode and peak ED census. Results Of 372 screened patients, 340 met eligibility and were analyzed (170 control, 170 ENAF). Timely ECG completion increased from 60.0% to 78.2% (adjusted odds ratio 2.31, 95% CI: 1.47–3.63; P < 0.001). Median door-to-troponin time fell from 50 to 39 min (P < 0.001); pain-relief success rose from 45.3% to 61.8% (P = 0.002). Documentation completeness improved by ten percentage points (P < 0.001) and median ED LOS decreased by 0.8 h (P = 0.01). Thirty-day MACE was similar between phases (15.3% vs. 12.9%; P = 0.49), and no serious adverse events were attributed to the protocol. Conclusions Augmenting ENAF with a structured clinical-needs module significantly accelerates ECG acquisition, improves other process metrics and enhances nursing documentation while maintaining patient safety. Adoption of this nurse-led approach could strengthen ED chest-pain pathways in comparable resource-constrained settings, and multicenter validation are warranted to establish generalizability.